Consumer Preference Model for Safe and Healthy Halal Culinary Zones in Indonesia: Integration of Functional Factors and Religious Values - Nursantri; Chuzaimah Batubara; Muhammad Arif (Yayasan Darussalam Bengkulu, 2026)
Background: The development of the halal industry in Indonesia reflects a shift in consumer behavior from merely emphasizing halal compliance toward broader considerations of safety and health. In response, the government introduced the Halal, Safe, and Healthy Culinary Zone (KHAS) to provide a standardized consumption environment. However, the KHAS concept has not been fully integrated into consumers’ daily preferences, creating the need to examine the factors influencing consumer preferences toward KHAS zones. Therefore, this study analyzes the effects of halal awareness, perceived safety, perceived health, and perceived price on consumer preferences, with religiosity as a moderating variable. Method: This study employed a quantitative approach with explanatory design. Data were collected through a survey of 255 urban Muslim respondents from generations X, Y, and Z in various regions of Indonesia that already have KHAS zones (Banda Aceh, Medan, Pekanbaru, Padang, Jakarta, Bandung, Yogyakarta, Semarang, and Samarinda). Data analysis utilized Structural Equation Modeling based on Partial Least Squares (PLS) using SmartPLS 4.0 software. Results: The results showed that halal awareness, health perception, and price perception had a positive and significant effect on consumer preferences in choosing KHAS zones. Conversely, safety perception was not found to have a significant effect on consumer preferences (p-value < 0.05). The model showed good goodness of fit with SRMR 0.061 and NFI 0.797. Conclusion: This study confirms that consumer preferences for the KHAS Zone are shaped by a combination of rational, psychological, and religious factors. The research model indicates that the halal consumption behavior of modern Muslim communities is no longer solely oriented toward normative compliance with product halal standards, but has evolved into a consumption pattern that takes into account health quality, convenience, economic value, and alignment with the principles of maqashid al-sharia